Nemške pesmi Daniela Lagkhnerja (1606) - Motnik, Marko (Časopis za zgodovino in narodopisje, 2023)
Born in Maribor in the second half of the 16th century, composer Daniel Lagkhner spent most of his life in the service of the Barons of Losenstein in the Lower Austrian town of Loosdorf and was actively involved in the local Protestant church community. In addition to three collections of Latin ecclesiastical texts, Lagkhner also published a hitherto almost unnoticed collection of German secular poems in 1606. This incompletely preserved musical print provides some interesting insights into the composer’s social milieu; but it also raises new questions about the origins, purpose, and use of the collection in the broader social context of the early 17th century.
Keywords: 16.st.; Lagkhner, Daniel; Maribor; nemške pesmi; protestantizem; skladatelji; Spodnja Avstrija